Upaya Meningkatkan Hasil Belajar PKn Melalui Model Pembelajaran Kooperatif Tipe Round Club Peserta Didik Kelas IVA SD Negeri 64/IV Kota Jambi - Efda Iryanti (Universitas Batanghari Jambi, 2019)
Research is backed by the fact that PKn is one of the lessons that are lacking in the hearts of learners. Because this learning is considered to be a difficult and boring lesson, it affects the low learning outcomes of learners. Based on observations that authors as teachers in elementary School 64/IV Jambi, especially class IV. A on PKn subjects that students ' learning outcomes are still low. Only 51.85% of learners reach the KKM 75. This study uses two-cycle class action research. Each cycle consists of four phases: design, activity and observation, reflection, and revision. The target of this research is class IV students. A in SD Negeri 64/IV Jambi City. Data obtained in the form of formative test result, observation sheet of teaching learning activities. From the results analysts gained that student learning results experienced an increase from the pre cycle until the II cycle, the pre-cycle (64.81%) With the submission of 51.85, Cycle I (72.41%), with 70.37 and cycle II (80.93%) With the 85.19 submission. The conclusion of this study is the cooperative learning Model of Round Club type can positively affect the outcome of students learning outcomes of class IV. A State Elementary School 64/IV Jambi City, and this learning model can be used as an alternative learning of PKn.